Building new spatial interaction models by using genetic programming and a supercomputer. - Diplock, G. (Environment & Planning A, 1998)
Part of a special section on geocomputation, which is defined as the process of applying computing technology to geographical problems. The writer outlines an application of a parallel genetic programming approach to discovering new spatial interaction models. He discusses how to develop new models by means of a machine-based inductive approach. He employs a Cray T3D parallel supercomputer with 512 processors to examine the potential of this approach to building computer models. His findings allude to the potential power of the method for applications where a considerable amount of data exists but where there are no suitable existing models or no good theoretical framework on which to base their development.